2018
DOI: 10.1097/j.pain.0000000000001288
|View full text |Cite
|
Sign up to set email alerts
|

Pain sensitization associated with nonresponse after physiotherapy in people with knee osteoarthritis

Abstract: In knee osteoarthritis (OA), pain sensitization has been linked to a more severe symptomatology, but the prognostic implications of pain sensitivity in people undergoing conservative treatment such as physiotherapy are not established. This study aimed to prospectively investigate the association between features of pain sensitization and clinical outcome (nonresponse) after guideline-based physiotherapy in people with knee OA. Participants (n = 156) with moderate/severe knee OA were recruited from secondary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 72 publications
3
78
0
2
Order By: Relevance
“…Unfortunately, this intervention was not sufficient to show a clinically meaningful difference in patient-reported outcomes and a statistically significant difference in proportion of OMERACT-OARSI responders in the intervention group compared to the usual care control group. However, the total proportion of responder in the intervention group (47%) is similar to previous RCTs applying the OMERACT-OARSI responder criteria to evaluate the effect of different physiotherapist led exercise interventions on knee OA [22][23][24].…”
Section: Discussionsupporting
confidence: 70%
“…Unfortunately, this intervention was not sufficient to show a clinically meaningful difference in patient-reported outcomes and a statistically significant difference in proportion of OMERACT-OARSI responders in the intervention group compared to the usual care control group. However, the total proportion of responder in the intervention group (47%) is similar to previous RCTs applying the OMERACT-OARSI responder criteria to evaluate the effect of different physiotherapist led exercise interventions on knee OA [22][23][24].…”
Section: Discussionsupporting
confidence: 70%
“…Recently, O'Leary et al [36] found that facilitated TSP and low PPTs were predictive of poor outcome for knee OA patients following physiotherapy. The current study further indicates that knee OA patients with facilitated TSP do not respond optimally to standard anti-inflammatory treatment, which is in line with a previous study regarding topical NSAIDs in knee OA [16].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Several studies have shown that the analgesic effects of NSAIDs plus paracetamol are superior to placebo [11,12,15,29,45]. The aim of the study was to investigate the value of mechanistic pain profiling and its predictive value after NSAIDs and paracetamol treatment as mechanistic pain profiling has previously been shown to identify poor responders to other standardized OA treatments [36,39,40,42,54]. Predicting poor NSAID treatment outcome is valuable as patients not responding adequately should not be treated with NSAIDs due the possible unwanted side effects.…”
Section: Limitationsmentioning
confidence: 99%
“…is similar to previous RCTs applying the OMERACT-OARSI responder criteria to evaluate the effect of different physiotherapist led exercise interventions on knee OA (22)(23)(24).…”
Section: Factors Associated With Completing the Exercise Programme (Imentioning
confidence: 56%